Effect of rooting media on flowering and yield of bidhan marigold varieties in West Godavari districts (open field) of Andhra Pradesh - VIJAY, J.; DORAJEERAO, A.V.D. (Journal of Ornamental Horticulture, 2025)
An experiment was carried out in factorial concept with two factors i.e., varieties at two levels and rooting media at eight levels thus making 16 combinations which were replicated twice. The effect of varieties, rooting media and their interactions were found to be significant with regard to days taken for first flower bud initiation, days taken for full flower opening, in situ longevity, days taken for 50% flowering, days taken for 100% flowering, duration of flowering, flower diameter, weight of 10-flowers, shelf life of flowers, number of flowers/ plant, flower yield/plant, flower yield/plot and flower yield/hectare. The variety Bidhan Marigold 1 recorded the minimum days for full flower opening (5.79 days), maximum duration of flowering (30.26 days), highest average weight of 10-flowers (7.18 g), highest shelf life of flowers (9.62 days), superior performance of number of flowers per plant (91.30 flowers per plant), highest flower yield per plant (437.75), flower yield per plot (15.29) and highest flower yield per hectare (15.29 t) whereas, the variety Bidhan Marigold 2 recorded the earliest flower bud initiation (37.96 days), maximum days for in situ longevity (20.22 days), lowest number of days for 50% flowering (48.01 days).